Analysis of Self‐selection Bias in a Population‐based Cohort Study of Autism Spectrum Disorders. Issue 6 (25th July 2013) - Nilsen, Roy M.; Surén, Pål; Gunnes, Nina; Alsaker, Elin R.; Bresnahan, Michaeline; Hirtz, Deborah; Hornig, Mady; Lie, Kari Kveim; Lipkin, W. Ian; Reichborn‐Kjennerud, Ted; Roth, Christine; Schjølberg, Synnve; et al.
Abstract Background This study examined potential self‐selection bias in a large pregnancy cohort by comparing exposure‐outcome associations from the cohort to similar associations obtained from nationwide registry data. The outcome under study was specialist‐confirmed diagnosis of autism spectrum disorders (ASDs). Methods The cohort sample (n = 89 836) was derived from the population‐based prospective Norwegian Mother and Child Cohort Study and its substudy of ASDs, the Autism Birth Cohort (ABC) study. The nationwide registry data were derived from the Medical Birth Registry of Norway (n = 507 856). The children were born in 1999–2007, and seven prenatal and perinatal exposures were selected for analyses. Results ASDs were reported for 234 (0.26%) children in the cohort and 2072 (0.41%) in the nationwide population. Compared with the nationwide population, the cohort had an under‐representation of the youngest women (<25 years), those who had single status, mothers who smoked during pregnancy, and non‐users of prenatal folic acid supplements. The ratios of the adjusted odds ratios (ORs) in the cohort over the adjusted ORs in the nationwide population were as follows; primipara pregnancy: 1.39/1.22, prenatal folic acid use: 0.85/0.86, prenatal smoking: 1.20/1.17, preterm birth (<37 weeks): 1.48/1.42, low birthweight (<2500 g): 1.60/1.58, male sex: 4.39/4.59 (unadjusted only); and caesarean section history: 1.03/1.04. Conclusions Associations estimated between ASDs and perinatal and prenatal exposures in the cohort are close to those estimated in the nationwide population. Self‐selection does not appear to compromise validity of exposure‐outcome associations in the ABC study.